Health Education - Open Textbook Library; College of the Canyons (Open Textbook Library, 2018)
Readers will learn about the nature of health, health education, health promotion and related concepts. This will help to understand the social, psychological and physical components of health.
Chapter 1: Introduction to Health -- Chapter 2: Psychological Health -- Chapter 3: Stress Management -- Chapter 4: Relationships and Communication -- Chapter 5: Gender and Sexuality -- Chapter 6: Sexual Health -- Chapter 7: Infectious diseases and Sexually Transmitted Infections (STI's) -- Chapter 8: Substance Use and Abuse -- Chapter 9: Basic Nutrition and Healthy Eating -- Chapter 10: Weight Management -- Chapter 11: Physical Fitness -- Chapter 12: Cardiovascular Disease, Diabetes, and Cancer -- Chapter 13: Environmental Health -- Chapter 14: Health Care Choices
In English.
Description based on online resource
Keywords: Biology -- Textbooks